Extruded filaments derived 3D printed medicated skin patch to mitigate destructive pulmonary tuberculosis: design to delivery. (1st February 2021) - Chaudhari, Vishal Sharad; Malakar, Tushar Kanti; Murty, Upadhyayula Suryanarayana; Banerjee, Subham
ABSTRACT: Background : Quercetin in combination with polyvinylpyrrolidone (PVP) was found to limit the spreading of necrosis to unaffected tissues in tuberculosis-infected mice. Therefore, we hypothesized that 3D printed medicated skin patch incorporated with a quercetin-PVP combination would provide an appropriate therapeutic drug concentration with desired sustained release profile. Research design and methods : We fabricated quercetin-PVP 40 extruded-filaments by hot-melt extrusion (HME) technique along with Eudragit® RSPO and tri-ethyl citrate and further printed it to make medicated skin patches using fused deposition modeling (FDM) based 3D Printing technology. Various characterizations were performed to optimize the 3D-printed patch formulation. Results : Patch formulation has been optimized for several characterization parameters and was further assessed using SEM, DSC, and XRD studies to confirm the conversion of crystalline quercetin into an amorphous form. Finally, the pharmacokinetic profile of an optimized patch was studied in rats showing prolonged Tmax, lowered Cmax, and reduced fluctuations in plasma concentrations till 18 days with single skin application of 3D-printed medicated patch. Conclusion : Overall data confirmed the feasibility of developing 3D printed medicated skin patches to provide plasma levels for continued 18 days in rats after a single application.